Treatment of Intrabony Periodontal Defects With Platelet-Rich Plasma Versus Platelet-Poor Plasma Combined With a Bovine-Derived Xenograft: A Controlled Clinical Trial - (:unkn) unknown (WILEY, 2011)
Background: The purpose of this study is to assess the healing outcomes of intrabony defects after treatment with platelet-rich plasma (PRP) versus platelet-poor plasma (PPP) combined with bovine-derived xenograft (BDX). Methods: Using a split-mouth design, a total of 79 intrabony defects with an intrabony component of >= 3 mm in 20 patients were treated either with PRP/BDX (group 1) or PPP/BDX (group 2). At baseline and 12 months after surgery, plaque and sulcus bleeding indices, probing depth (PD), relative attachment level, recession, and probing and radiographic bone levels were recorded. Results: After 12 months, groups 1 and 2 presented a mean PD reduction of 3.87 +/- 0.86 and 3.76 +/- 0.80 mm, recession of 1.35 +/- 0.68 and 1.58 +/- 0.54 mm, attachment gain of 2.51 +/- 0.97 and 2.18 +/- 0.87 mm, clinical bone gain of 2.18 +/- 0.86 and 2.09 +/- 0.89 mm, and radiographic bone gain of 2.11 +/- 0.87 and 2.19 +/- 0.96 mm, respectively. Intergroup differences were found to be insignificant. Conclusions: Within its limits, these results suggest that the outcomes of the treatment after PRP/BDX and PPP/BDX applications in intrabony defects are similar. When the platelet counts are taken into consideration, PPP seems to demonstrate similar clinical efficacy as the PRP. J Periodontol 2011;82:837-844.
Keywords: Chronic periodontitis; clinical trial; periodontal bone loss; platelet-rich plasma; regeneration; GUIDED TISSUE REGENERATION; CELLS-IN-VITRO; EXPANDED POLYTETRAFLUOROETHYLENE MEMBRANES; GROWTH-FACTOR-BETA; BIOACTIVE GLASS; LIGAMENT CELLS; FIBRIN GLUE; SPLIT-MOUTH; BIO-GIDE; COMBINATION